Prevalence of latent tuberculosis in medical students - Yumpo-Castañeda, Daniel Hernan (2019)
Objective. To determine the prevalence of latent tuberculosis or infection by Mycobacterium tuberculosis among medical students. Material and Methods. A prospective, cross-sectional study was carried out among randomly assigned medical students from the 1st, 6th and 10th semesters in the School of Medicine of the Universidad Continental, Huancayo (central Andean region of Peru, 3 259 meters above sea level). Results. Seventy one students, 46 women and 25 men were included. A data collection card was used and the PPD test using the Mantoux technique was applied, which was evaluated at 72 hours. It was found a total prevalence of 15,49 % for TB infection, males 24% and females 10,87 %. By semesters were: In the 1st: 17,24 %, in the 6th: 3,07 %, and in the 10th: 33,33 %. Conclusions. The highest prevalence of latent tuberculosis was in males and in students with more study years and with longer hospital exposure.